Critical Communication Theory: Power, Media, Gender, and Technology - Jansen, Sue Curry (Rowman & Littlefield Publishers, 2002)
Critical theorist, feminist, and censorship expert Sue Curry Jansen brings a fresh perspective to contemporary communication inquiry. Jansen engages two key questions at the heart of a critical politics of communication: What do we know? And how do we know it? The questions are not unique to our era, she notes, but our responses to them are our own. Looking at issues of globalization, science, politics, gender, social inequality, and other social formations that shape our world, this insightful book advocates a new agenda not only for communication research, but also for the writing_and language_that comes out of it.